Effects of year of post‐secondary study on reading skills for L1 and L2 speakers of English. (26th January 2022) - McCarron, Sean Patrick; Kuperman, Victor
Abstract : Background: Previous studies show that students improve communication skills throughout post‐secondary study proportionately to first‐year ability, yet important questions remain. How does post‐secondary affect the development of reading comprehension and related skills? How does this development vary between L1 and L2 speakers, and how much change occurs each year? Methods: We administered a cross‐sectional battery of tests of reading proficiency to undergraduate university students in all years of study. The tests included measures of reading comprehension and multiple component skills: vocabulary, spelling, print exposure, reading habits and motivation. Results: Results show that year of study confers a direct effect on component skills of reading. Skill trajectories of L1 and L2 students vary widely – across all skills tested, L1 students in Year 4+ show an average advantage of 12.60 percentile points compared with those in Year 1, whereas the average advantage of L2 students in Year 4+ over Year 1 peers is 29.20 percentile points. No difference between L1 and L2 readers, or between years of study, was observed in reading comprehension. Conclusions: Post‐secondary education confers sizable benefits to all examined component skills of English reading, especially in L2 students. While L2 students in Year 1 are disadvantaged in most skills, L2 students in Year 4+ close the performance gap with L1 speakers on all skills. This suggests an 'anti‐Matthew' effect, with most benefits seen in the initially underperforming population. These findings quantify the effectiveness of university itself and also its differential impact on students with different language backgrounds. The apparent dissociation between a change in component skills of reading and stability in reading comprehension scores remains puzzling: we outline avenues for further investigation of this issue. Highlights: What is already known about this topic Students generally improve throughout university proportionately to ability in first year ('the Matthew effect'). L2 speakers generally begin university with lower literacy skills. What this paper adds Each year of study develops component skills of reading but has no direct effect on reading comprehension. We provide cross‐sectional evidence that L2 students in later years of study have a greater advantage in most component skills of reading than L1 peers (an 'anti‐Matthew effect') – resulting in L2 speakers 'closing the gap' with L1 students. Implications for theory, policy or practice Explicit and direct instruction in the component skills of reading – primarily, vocabulary size and word decoding – may lead to important gains in these skills beyond the typical improvements seen throughout university study.